The effects of fluoxetine, tianeptine and placebo on premenstruel syndrome in chronic headache sufferers - Akyol, A; Tezcan, AE; Baydas, G; Onal, SA; Yucel, O; Mungen, B (Monduzzi Editore, 1996)
The aim of this study to investigate the effectivenes of Fluoxetin, Tianeptine, and placebo on premenstruel syndrome (PMS) with chronic headache. We tried to show whether the pathophysiology of chronic headache with PMS is related to serotonin release or reuptake, in human brain. Parameters analyzed for daily dose of fluoxetine, tianeptine, and placebo were intensity, frequency, duration of headaches and life quality with Picirra Pain Measurement, Hamilton Depression Rating Scale (HDRS) and Hamilton Anxiety Rating Scale (HARS) and these parameters were analyzed. Adverse effects of medication were also analyzed. Both contrast effectual drugs improve the headache in PMS, suggest that serotonin depletion alone cannot be the sole etiology of the chronic daily headache syndrome and further investigations must be done to prove the etiology of chronic tension-type headache in PMS.
7th International Symposium on the Pain Clinic -- OCT 02-06, 1996 -- ISTANBUL, TURKEY